Thesis Guideline: Bachelor of Business Engineering - Nawanir, Gusman; Lee, Khai Loon; Mahmud, Fatimah; Lee, Chia Kuang (UMP Publisher, 2019)
Thesis (BPN4026) is intended to expose final year students on the process of conducting academic case-based research in the area of Business Engineering. Generally, thesis provides them with an opportunity to demonstrate ideas, research skills, and creative abilities. The specific objectives of this course are as follows: 1. To develop the students’ basic skill of research. 2. To expose the students in conducting literature review from research materials, such as journals, internet sources, magazines, etc. 3. To have insight on research methodology in the areas of students’ interest. 4. To assist the students in data analysis. 5. To produce an acceptable thesis. 6. To build student’s self-confidence, communication, presentation, writing and time management skills. In order to achieve the above objectives, this guideline is prepared for the final year students of Bachelor of Business Engineering with Honours in conducting their case-based research within one semester (i.e., semester eight). It guides the students to meet the minimum requirement of thesis, starting from proposing research idea until final reporting, besides as a logbook to record their research activities and progress. We expect that this guideline shall be utilized as a standard to produce high quality of researches and theses. All the best!